2,2 `-Iminodiethanaminium 2,2 `-(disulfanyldiyl)dibenzoate dihydrate - Broker, G.A.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
In the title hydrated salt, C4H15N32+center dot C14H8O4S2-center dot 2H(2)O, the dication (with both terminal -NH2 groups protonated) adopts a U-shaped conformation, the N-amine-C-C-N-azanium torsion angles being 57.9 (6) and 60.3 (6)degrees. The dianion is twisted: the central C-S-S-C torsion angle is 81.3 (2)degrees and the dihedral angle between the benzene rings is 85.4 (3)degrees. In the crystal, a chain in the a-axis direction mediated by water-carboxylate O-H center dot center dot center dot O hydrogen bonds through a sequence of alternating 12-membered {center dot center dot center dot OCO center dot center dot center dot HOH}(2) and eight-membered {center dot center dot center dot O center dot center dot center dot HOH}(2) synthons occurs, which involves only one of the carboxylate residues. The second carboxylate residue participates in N-H center dot center dot center dot O hydrogen bonding, generating a three-dimensional network, along with azanium-water N-H center dot center dot center dot O hydrogen bonds.